STUDI EKSPERIMENTAL PERPINDAHAN KALOR KONVEKSI, PENURUNAN TEKANAN DAN FAKTOR GESEKAN PADA ALAT PENUKAR KALOR MENGGUNAKAN MICRO-FIN TUBE - Ahmad Imam Rifa’i; Budi Kristiawan; Agung Tri Wijayanta (Universitas Sebelas Maret, 2019)
Micro-fin is the popular technique for increasing heat transfer performance of the heat exchangers. In this research, the heat transfer coefficient of water inside counter-flow heat exchangers with micro-fin was investigated by experiment at the Reynolds number (Re) was varied from 4000-10,000. The results show that the heat transfer coefficient increase with increasing Reynolds number. Furthermore, effect helical micro-fin increasing pressure drop and friction factor at turbulent flow region.